WOMAN RESISTENCE IN A CHINESE DRAMA SERIES "SCARLET HEART 步步惊心 (BU BU JING XIN)" - Ramadhanty, Ardhia Aulia; Fatmawati, Fatmawati; Ningsih, Tri Wahyu Retno (Marwah: Jurnal Perempuan, Agama dan Jender, 2024)
Abstract:The aim of this study is to investigate the manifestations of resistance displayed by the main female character in the television series "Scarlet Heart 步步惊心" (Bu Bu Jing Xin), particularly Ruoxi/Zhang Xiao, using the feminist approach to power proposed by Naomi Wolf (1993). The method employed in this study was qualitative descriptive, with data sources consisting of words, phrases, sentences, and discourses encompassing elements of female resistance. The findings indicate that the main female character in this drama, Ruoxi/Zhang Xiao, exhibits resistance in alignment with the feminist perspective on power articulated by Naomi Wolf (1993), namely: 1) Affirming that men and women have equal worth in life. 2) Women have the right to take control of decisions that affect their lives. 3) Women's experiences deserve to be valued. 4) Women have the freedom to express themselves without hindrance, and 5) Women have the right to pursue and advocate for their needs as desired.Keywords: Resistance; Women; Drama; Feminism.